2021
DOI: 10.1007/s10796-021-10121-z
|View full text |Cite
|
Sign up to set email alerts
|

E-Government and Entrepreneurship: Online Government Services and the Ease of Starting Business

Abstract: Governments around the world are making active efforts to encourage entrepreneurship. At the same time, governments have also embraced digital technology, particularly the online delivery of government services. This paper examines the effect of offering government services online on the ease of setting up new businesses around the world. Panel data from almost 200 countries between 2002 and 2010 were assembled from multiple public databases and analyzed with fixed-effects regression models in STATA to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…This could happen when such modernization eases the cost, time and procedures of formalizing businesses, and makes access to business‐related information and policies accessible and the taxation process more efficient and effective. This is consistent with the findings and arguments of Abu‐Shanab and Osmani (2019) and Das and Das (2021). The estimated result is also quite sizable: for every 0.1 point increase in digitalization, the shadow economy shrinks by 4%, from columns 1 to 6.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This could happen when such modernization eases the cost, time and procedures of formalizing businesses, and makes access to business‐related information and policies accessible and the taxation process more efficient and effective. This is consistent with the findings and arguments of Abu‐Shanab and Osmani (2019) and Das and Das (2021). The estimated result is also quite sizable: for every 0.1 point increase in digitalization, the shadow economy shrinks by 4%, from columns 1 to 6.…”
Section: Resultssupporting
confidence: 93%
“…When associated with the shadow economy, digitalization or e‐government present various potentials for curtailing the extent of the shadow economy. For instance, (Das & Das, 2021) showed that the more digitalized government services are, the easier it becomes for formal ventures to be established. By implication, the extent of informal economic ventures will reduce.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From the macro perspective, previous researchers have studied the mechanisms of the digital economy promoting industrial ecological integration and innovation, thus achieving the optimization and upgrading of industrial structure and high-quality economic development. For example, Estevez and Janowski (2013), Almeida and Zouain (2016), and Das and Das (2022) study the role of the digital economy in economic development from the perspectives of sustainable development goals, business environment, financial development, international trade, entrepreneurship, respectively. These studies show that digital technology provides opportunities for innovation and promotes the organic integration between green technology innovation and green economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dhaoui (Dhaoui, 2022), E-government promotes sustainable economic development and creates opportunities for innovation. Das (Das and Das, 2022)believes that the development of E-government has made it easier to start a new business and initiate innovative ventures. Taken all the above together, there is an inseparable correlation between economic growth and environmental pollution (Zhang and Ran, 2023).…”
Section: Introductionmentioning
confidence: 99%